Upaya Meningkatkan Hasil Belajar IPS Dengan Model Pembelajaran Kooperatif Tipe STAD Pada Kelas IV MI Terpadu Al Muttaqin Sawangan - Anisa Nur Azizah (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
This study aims to improve social studies learning outcomes by using the STAD typecooperative learning model for the fourth grade students of MI Terpadu Al Muttaqin,Sawangan District, Magelang Regency. The research subjects were 4th grade students ofthe Integrated MI Al Muttaqin, Sawangan District, Magelang Regency which consisted of14 boys and 4 girls. Data collection techniques are documentation, observation, and tests.The analytical technique used is comparative descriptive. The results showed that theSTAD model could improve the social studies learning outcomes of the 4th grade studentsof MI Terpadu Al Muttaqin Sawangan District, Magelang Regency. an increase in cycle 1to 89% of students who completed, then in cycle 2 it increased to 94%. Learning with theSTAD type cooperative model needs to be implemented in social studies learning in theclassroom, because the learning model can improve student learning outcomes. Teachersmust be able to motivate students to be more active in learning by conducting intensiveguidance.